Assessment of Digital and Financial Inclusion of women farmers/ entrepreneurs/ women-led agri startups - Shukla, Pragati; Veenita Kumari; P. Sai Charitha (Journal of Agricultural Extension Management, 2025)
Financial literacy is defined as a combination of financial awareness, knowledge, skills, attitude and behaviour necessary to make sound financial decisions and ultimately achieve individual financial well-being. A few G20 countries like Australia, Canada, France, Japan and the United Kingdom (UK) have achieved close to 100 percent financial inclusion of women in certain parameters such as account ownership and use of debit/credit cards. India, in 2021, had an insignificant gender gap in terms of account ownership with around 77 percent of women (almost equal number as men) having an account with a financial institution. Skill in the use of digital device and tools is affected by due to lack of access & awareness, less exposure to digital literacy and less skill in the use of digital devices/ gadgets. Purchasing a device/ gadget is still a household decision and women are generally neither a user or a dormant user nor an influencer in the decision making process of purchase of these devices. Womens’ didn’t know the difference between a PAN card and an ATM card. They prefer to withdraw money through Aadhaar Card from Community Service Center (CSC), which was more convenient to them. Trained women were better knowledgeable of digital and financial inclusion. It is therefore necessary to give hands-on skill to women on digital and financial inclusion so that they become more confident in the use, access and knowledge on these technologies